Belt and Road Environmental Implications for South Asia - Ali, Majid; Faqir, Khan; Haider, Bilal; Shahzad, Khurram; Nosheen, Nosheen (Frontiers in Public Health, 2022)
The Belt and Road Initiative (BRI) can play a significant role in the sustainable development of South Asia if implemented properly. Apart from the economic, trade, and cultural benefits associated with this huge infrastructure, little is known about its environmental impact on South Asia. This study looks closely at the potential impact of the BRI on the South Asian environment. This research is based on government-issued environmental policies, peer-reviewed literature, media articles and reports. It has been suggested that the BRI could have a negative impact on the South Asian environment, provided it does not consider the Paris agreement with its partners in the region. This study suggests that partner countries should adapt the BRI project to the principles of environmental impact assessment.